Association of digital screen use during recess with physical activity behaviours in 10-year-old to 17-year-old Danish adolescents: a population-based cross-sectional study - Soren Brage; Jens Troelsen; Anders Grøntved; Peter Lund Kristensen; Jan C Brønd; Anne Kær Gejl; Niels C Møller; Kristian T Larsen; Sofie Koch; Natascha H Pedersen (BMJ Public Health, 2025)
Background The widespread ownership of digital devices among adolescents presents challenges and opportunities in schools, particularly during recess. This study aimed to examine the association of screen use during recess with physical activity behaviours.Methods The study was based on a population-based cross-sectional study including 1347 adolescents from 28 schools (2017–2018). Physical activity behaviours were assessed using thigh-attached accelerometers, worn 24/7 for up to 6 weekdays and 2 weekend days. We examined accelerometer data for all recess periods, aligned with each adolescent’s school schedule, along with leisure-time activity from the same days. Physical behaviours were classified during recess and leisure-time behaviour (negative control). Frequency of screen use during recess was based on self-report using a 5-point ordinal scale.Results Greater frequency of screen use during recess was associated with less time engaged in physically active behaviours and more time spent sitting, consistent with dose-dependent associations. In multivariable-adjusted analysis, adolescents with no screen use during recess spent an absolute 11.1% (95% CI 5.4 to 6.8) more of their recess time being physically active compared to those with frequent use. Based on the mean recess duration observed in the sample, adolescents not using screens during recess engaged in physical activities for an average of 44.9 min per day (95% CI 42.3 to 47.6), compared with 35.1 min (95% CI 26.0 to 44.3) for frequent screen users. Leisure time activities, used as a negative control, showed no link to screen use during recess.Conclusion Increased screen use during recess was associated with lower physical activity levels. These findings suggest that regulating digital device use during recess could enhance physical activity among adolescents.